Unveiling Success: Exploring the Impact of Training and Commitment on Madrasah Tsanawiyah Principal Performance - Djalilah, Sitti Rohmi; Muzakar, Abdullah; Suhardi, Muhamad; Kartiko, Ari (Nazhruna: Jurnal Pendidikan Islam, 2024)
This article delves deep into the complex web of relationships between training, commitment, and performance among heads of private Tsanawiyah Madrasahs in the beautiful West Lombok Regency, West Nusa Tenggara Province. Using a quantitative approach reinforced by path analysis, the researchers uncovered the causal relationships that shape the madrasah leadership landscape. The study underwent rigorous validation by drawing insights from a carefully curated data set covering over 170 madrassa heads, meticulously collected through customized questionnaires. It emerged as a beacon of reliability and validity. Through the lens of descriptive and inferential statistics, the findings of this study not only highlight the transformative potential of training and commitment but also offer a roadmap for education policymakers and school principals across the country, thereby sparking a collective effort to achieve excellence in madrasa education. Although rooted in the local context of West Lombok Regency, the implications of this research have an impact far beyond the district's borders, marking a new era of educational innovation and progress. In essence, this study underscores the importance of disentangling the complex factors that shape the principal performance landscape to realize a brighter future for madrasa education nationally.